Effectiveness Of Young Papaya Book Consumption To Increasing Breast Milk Production In Breastfeeding Mothers - Masniar Hutahayan; Ita Herawati (CV. Inara, 2023)
In 2020 UNICEF reported that the average coverage of exclusive breastfeeding in the world for infants aged 0-6 months only reached 38%. In Indonesia in 2018, the coverage rate for exclusive breastfeeding was 52%, in West Java Province in 2020 the coverage for exclusive breastfeeding for infants was 72.6%. The low coverage of exclusive breastfeeding can be caused by various factors, one of which is the production of breast milk which is not optimal, so that many babies have less nutritional needs because mothers cannot provide maximum breast milk according to the nutritional needs of babies. Breast milk production can be increased by doing complementary therapies, one of which is consuming young papaya stew. To determine the effectiveness of consuming young papaya stew to increase the smooth production of breast milk in nursing mothers. Quasy experiment with one group pretest-posttest design. The sample in this study were all postpartum mothers at PMB Midwife Masniar in November 2022 as many as 30, the sampling technique was total sampling. The smooth distribution of milk production before consuming young papaya stew was mostly substandard 60.0% and after consuming unripe papaya stew most of it was smooth 63.3%. There is an effectiveness of consuming young papaya stew to increase the smooth production of breast milk in nursing mothers (p value 0.000). There is the effectiveness of consuming young papaya stew in increasing the smooth production of breast milk in nursing mothers. It is hoped that midwives can provide midwifery care for postpartum mothers who experience breast milk difficulties by consuming young papaya stew.